The bli regulon - a network of blue light inducible genes of N. crassa - N. N. PANDIT; V. E. A. Russo (Fungal Genetics Reports, 1991)
Several physiological responses of N. crassa are observed when this fungus is exposed to blue light. Here, we do not intend to make a comprehensive list of all the light effects observed so far in N. crassa (for a review, see Degli Innocenti and Russo 1984. In "Blue Light Effects in Biological Systems" ed. H. Senger, Springer-Verlag. pp 213-219.), but point out only the underlying themes. First, the time interval between the light stimulus and the observed response can be very different, and ranges from a few minutes to several hours - or even days - depending on the nature of the physiological response in question.